Economic evaluation of strategies for managing crying and sleeping problems. Issue 1 (1st January 2001) - Morris, S; St James-Roberts, I; Sleep, J; Gillham, P
Abstract : AIMS: To estimate the financial cost to the NHS of infant crying and sleeping problems in the first 12 weeks of age and to assess the cost effectiveness of behavioural and educational interventions aimed at reducing infant crying and sleeping problems relative to usual services. METHODS: A cost burden analysis and cost effectiveness analysis were conducted using data from the Crying Or Sleeping Infants (COSI) Study, a three armed prospective randomised controlled trial that randomly allocated 610 mothers to a behavioural intervention (n = 205), an educational intervention (n = 202), or existing services (control, n = 203). Main outcome measures were annual total cost to the NHS of infant crying and sleeping problems in the first 12 weeks, and incremental cost per interruption free night gained for behavioural and educational interventions relative to control. RESULTS: The annual total cost to the NHS of infant crying and sleeping problems in the first 12 weeks was £65 million (US104 million). Incremental costs per interruption free night gained for the behavioural intervention relative to control were £0.56 (US0.92). For the educational intervention relative to control they were £4.13 (US6.80). CONCLUSIONS: The annual total cost to the NHS of infant crying and sleeping problems is substantial. In the cost effectiveness analysis, the behavioural intervention incurred a small additional cost and produced a small significant benefit at 11 and 12 weeks of age. The educational intervention incurred a small additional cost without producing a significant benefit.